Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi Kota Madiun Tahun 1990-2014 - Setiawan, Rachmadi Budi; , Dr. Dayyono S., MEc (2016)
This study aimed to analyze the influence of the population, by expense government, and local taxes to regional gross domestic product Madiun District in 1990-2014, either partially or simultaneously. The benefits of this research is for consideration and decision making, in order to increase economic growth in the Madiun District The method of analysis using a quantitative approach with sample data of population, expense of government, and local taxes on regional gross domestic product Madiun District in 1990-2014. The analysis tool used is multiple linear regression model with Ordinary Least Square method (OLS). Based on the results of analysis show that the population has no effect on Economic Growth in the Madiun District; Growth in expense government affect the economy in the Madiun District; Local taxes affect the economic growth in Madiun District; As well as are all variable of the population, expense government and taxes has affect on the Economic Growth in the Madiun District.